2023
DOI: 10.3390/antiox12061231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Filtration Process on Oxidative Stability and Minor Compounds of the Cold-Pressed Hempseed Oil during Storage

Abstract: Cold-pressed hempseed oil (HO) has been increasingly exploited in the human diet for its excellent nutritional and healthy properties. However, it has a high content of polyunsaturated fatty acids (PUFAs) and chlorophylls, which inevitably accelerate its oxidative deterioration, especially in the presence of light. In this scenario, the filtration technology may ameliorate the oxidative stability of the oil, with positive effects on its nutritional quality and shelf life. Therefore, in this study, the oxidativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…In the case of BE3, this is due to there being too large of a disproportion between the parameters of the oils obtained in the CP and HP variants, especially considering the ratio of removed chlorophylls to carotenoids. Referring to the obtained results of the work of Lo Turco et al [45], where it was found that the reduction in natural dyes occurs at the stage of oil filtration, it can be concluded that BE4 (2.5%) has poor adsorption properties regarding carotenoid dyes. BE1, BE6, and BE7 at doses of 5.0% were the most effective at removing natural dyes (blue field in Figure 2b).…”
Section: Resultsmentioning
confidence: 81%
“…In the case of BE3, this is due to there being too large of a disproportion between the parameters of the oils obtained in the CP and HP variants, especially considering the ratio of removed chlorophylls to carotenoids. Referring to the obtained results of the work of Lo Turco et al [45], where it was found that the reduction in natural dyes occurs at the stage of oil filtration, it can be concluded that BE4 (2.5%) has poor adsorption properties regarding carotenoid dyes. BE1, BE6, and BE7 at doses of 5.0% were the most effective at removing natural dyes (blue field in Figure 2b).…”
Section: Resultsmentioning
confidence: 81%
“…For the extraction of tocopherols, 2 g of each freeze-dried PBM was mixed with 4 mL of n-hexane in a dark tube, stirred, and added with further 2 mL of methanolic KOH. Then, the mixture was stirred and centrifuged for 10 min at 4000× g at 4 • C. The supernatant was filtered through a 0.2 µm nylon filter, transferred into an amber vial, and analyzed by high-performance liquid chromatography coupled to a fluorescence detector (HPLC-FD) (Shimadzu, Milan, Italy) according to a protocol already proposed by Lo Turco and colleagues [31]. A LiChrosorb Si 60 (5 µm) column (4.6 mm I.D.…”
Section: Tocopherolsmentioning
confidence: 99%
“…The results of the analysis of the content of pigments and polyphenols are included in Table 2. Chlorophyll has a dual role: in daylight, it can act as a pro-oxidant causing oxidative instability, color change, and generally diminishing the nutritional attributes of the oil, but on the other hand, it can also act as an antioxidant agent in the dark [38,39]. The content of chlorophyll in oils can be very diverse and depends on the degree of maturity of the seeds, harvesting conditions, and also depends on conditions of drying and storage.…”
Section: Pigments and Total Phenols Content In Nc-cpro And C-cpromentioning
confidence: 99%